Overcoming Barriers, Building on Strengths: Maine Women Look at Aspirations - Pohlmann, Lisa; Rand, Kay; Lachance, Laurie; Stark, Francine; Nardone, Gilda (Maine Policy Review, 1997)
There is widespread belief in Maine that the aspirations of both young people and adults fall below much of the rest of the nation. Implicit in this perspective is the idea that aspirations must be raised if Maine is to prosper economically. Yet opinions differ about the definition of "aspirations," whether that definition may be expected or permitted to vary by county or region of the state, what factors contribute to the problem being identified as a lack of aspirations, and whether rural parts of Maine and women are at a particular disadvantage. In an effort to further the dialogue on these issues, the Maine Center for Economic Policy convened a round-table discussion in June, moderated and edited for Maine Policy Review by Lisa Pohlmann. The four participants are women who grew up in rural Maine and retain ties and allegiances to those roots. They have attained significant leadership positions within their fields and are respected widely for their many achievements and contributions to the public good. Their conversation was informal, candid, and spanned numerous issues. Here, their comments have been organized around a number of themes that emerged from the content of those discussions.